English Learning Assistance Using Interactive Media for Children with Special Needs to Improve Growth and Development - Wanti, Linda Perdana; Romadloni, Annisa; Somantri, Oman; Sari, Laura; Prasetya, Nur Wachid Adi; Johanna, Anne (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Children with special needs (ABK) are children who are in several ways different from other children in general. Among the crew members are Special Children (ALB), which consists of children who are blind, deaf, mentally retarded, quadriplegic, mentally disabled and double disabled. Some of the main things that need to be considered in the learning process for ALB are teachers, learning methods, learning approaches, infrastructure and learning support media (teaching aids). Purpose. The purpose of this community service activity is to solve the problems faced by partners in the English learning process, namely when a disorder results in disruption in daily functioning, especially in learning, the student requires special services (children with special educational needs) and requires specific learning methods in addition to appropriate and interactive learning media. Method. The solution offered to overcome this problem is the optimization of teaching methods. The recommended approach in the English language assistance activities for the Cilacap State Polytechnic PkM Team is in the form of prompts and demonstrations. Meanwhile, teaching English can use total physical response (TPR) by maximizing lip reading technique in addition to maximizing the use of flash cards to attract students' interest and focus. Results. The results obtained from this community service activity are increasing the ability of children with special needs to say a few simple words in English. The growth and development of children with special needs increase after the community service activities are completed. This is shown from the evaluation results carried out by the service team by conducting a post-test on ABK. Conclusion. To get significant results, namely increasing the growth and development of ABK, especially in the pronunciation of words in English, it is better if this activity is carried out regularly in the future.